An assessment of the usefulness of spatial agricultural land resource digital data for agritourism and ecotourism - Mugadza, Precious (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Agricultural Economics))—University of Stellenbosch, 2005.